Drivers of Marketing Innovation in Portuguese Firms - Jacinta Moreira; Maria Jose Silva; Jorge Sim\~oes; Gast\~ao Sousa (Amfiteatru Economic Journal, 2012)
This article aims at identifying and analyzing the drivers of innovation capacity of marketing in the context of Portuguese firms. From this standpoint, a theoretical framework is considered, which comprises the characterization of marketing innovation, as well as the determinants that underlie it. Based on the literature several research hypotheses are formulated, which are tested using secondary data provided by the “Observatório da Ciência e do Ensino Superior - OCES” - Observatory of Science and Higher Education, belonging to the “4 Inquérito Comunitário à Inovaç\~ao – CIS 4”- 4th Community Innovation Survey-CIS, supervised by EUROSTAT. The method used is the logistic regression model. The results show that the variables included in the factor R&D pertaining to internal R&D activities, acquisition of machinery, equipment and software, acquisition of other external knowledge and performance of other procedures, and the factor marketing activities, influence the propensity of firms to innovate in marketing.
Keywords: O31; M31; 330; innovation; marketing innovation; innovative capacity; Community Innovation Survey